Perbandingan antara Campuran Pasir Baik dengan Pasir Buruk pada Perbaikan Tanah Dasar Jalan Terhadap Daya Dukung Setelah Dilakukan dan Tidak Dilakukannya Swelling Potential Ditinjau Terhadap Tebal Perkerasan Jalan - Taufiq Qurrahman; Iswan Iswan; Rahayu Sulistyiorini (Jurnal Rekayasa Sipil dan Desain, 2021)
Swelling of clay soil has an impact on building construction. The problem that occurs in Marga Kaya Village, in the rainy season the soil is mushy and the carrying capacity becomes low so that the road is bumpy and the road body decreases. This study uses good sand stabilization material and bad sand with a mixture variation of 5%, 10% and 15% This study aims to find out the thick decrease in road pavement from each addition of mixed variations. Cbr results unsoaked and soaked maximum good sand occurs in a mixture of sand 15% with a value of 14.2% and 3.2%. The thickness of pavement on CBR unsoaked and soaked sand is well efficient on a mixture of sand 15% with a thickness of D1 = 2.25 cm, D2 = 20 cm and D3 = 10 cm, and soaked D1 = 8.75 cm, D2 = 20 cm and D3 = 10cm. Cbr unsoaked and soaked maximum value of bad sand occurs in 15% sand mixture with values of 13.9% and 2.6%. Thickness of pavement on CBR unsoaked and soaked bad sand maximum on the sand mixture 15% with thickness D1 = 2.5 cm, D2 = 20 cm and D3 = 10 cm, and soaked with thickness D1 = 9.25 cm, D2 = 20 cm and D3 = 10 cm. The value of swelling decreased from 11.4% to 5.7% and 8% in the addition of sand 15%.